Pengaruh Pembelajaran Berbasis Portofolio dan Kemampuan Awal Terhadap Hasil Belajar Mahasiswa Prodi PIAUD - Rohani, Rohani; Kesumawati, Tri Indah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2018)
This paper organizes about the effect of portofolio-based learning and the basic ability toward the result of learning media on students of Islamic Education Early Childhood study program, Faculty of Science and Teacher Training , State Islamic University of North Sumatera. The type of this research is quantitative research which is uses experiment form. The subject in this research is 70 third semester PIAUD students. The instrument that is used in this research is writing. The current data analysis is: analysis of two-way variance. The results of the study have showed that: (1) Students' learning outcomes using portofolio-based learning is better than student learning outcomes using conventional learning. (2) the basic ability influences the improving of student learning outcomes in mastering learning media. (3) Students' learning outcomes that has high ability in basic learning with portofolio based learning are different to the fact and significant to the other group.